Pengaruh Model Continuity of Care dalam Asuhan Kehamilan dan Persalinan terhadap Luaran Bayi Baru Lahir - Foranci, Yoki; Nontji, Werna; Arifuddin, Sharvianty (Journal of Telenursing (JOTING), 2023)
The aim of this research is to analyze the influence of the continuity of care model in pregnancy and childbirth care on the outcomes of newborn babies. The research method used is quasi-experimental with the Posttest-Only Control Design method. The research was carried out in the working area of the Weru and Danowudu Bitung Community Health Centers, North Sulawesi, from 16 March to 16 June 2023. The population was 173 respondents and the sampling technique, namely consecutive sampling, obtained 70 pregnant women divided into 2 groups, 35 each for the intervention group and 35 for the intervention group. for the control group. The results of the research show that the probability value in the chi-square test is 0.007 in the intervention and control groups, where this value is smaller than the standard significant value of 0.05, which means there is a significant influence from the results of the Continuity of Care model in pregnancy and delivery care on the outcomes of new babies. born. The conclusion obtained is that the influence of continuity of care in pregnancy and childbirth care can influence the outcomes of newborn babies. So to improve and maintain the quality of services for pregnant women, giving birth, BBL, it is necessary to provide continuous midwifery care. Keywords: ANC, Continuity of Care, Pregnant Women, Baby Outcomes